Impact of ICT as effective teaching- learning in higher education institutions in India - Bhinde, Ramesh (International Journal of Informatics and Communication Technology (IJ-ICT), 2021)
The aim of this paper is to examine role of ICTs in teaching-learning in higher education in India. ICT-Based education is a system of instruction that involves combination of computers and communication technologies. Information and Communication Technology (ICT) and in current trend ICT has become a common platform for majority population all over the globe. Web application and multimedia technologies have revolutionized educational field.Hence ICT plays a vital role in the field of Education especially in Higher Education. ICT Integration is important in combating digital divide, bringing about digital opportunity and paradigm shift from teacher centered to student centered learning, whereby the teacher passes the information quicker and in a more understandable manner.Implementation of ICTs, empowering teachers and supporting them in their engagement with students in learning. There are endless possibilities with the integration of ICT in the higher education system.Â